Reduced sphingolipid hydrolase activities, substrate accumulation and ganglioside decline in Parkinson’s disease - Huebecker, M; Moloney, EB; van der Spoel, AC; Priestman, DA; Isacson, O; Hallett, PJ; Platt, FM (BioMed Central, 2019)
Background: Haploinsufficiency in the Gaucher disease GBA gene, which encodes the lysosomal glucocerebrosidase GBA, and ageing represent major risk factors for developing Parkinson’s disease (PD). Recently, more than fifty other lysosomal storage disorder gene variants have been identified in PD, implicating lysosomal dysfunction more broadly as a key risk factor for PD. Despite the evidence of multiple lysosomal genetic risks, it remains unclear how sphingolipid hydrolase activities, other than GBA, are altered with ageing or in PD. Moreover, it is not fully known if levels of glycosphingolipid substrates for these enzymes change in vulnerable brain regions of PD. Finally, little is known about the levels of complex gangliosides in substantia nigra which may play a significant role in ageing and PD.